(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
When comparing two works, that are dissimilar in terms of what we will call here the linguistic gesture, but similar in terms of their fundamental understanding of the concept with respect to its function, the need to expand the access to such phenomena becomes clear, and to also include the key analytical moment of the mood of the language. The purpose of this analysis is to achieve expansion, from the proposed ontological starting point in Being and time, to take it to a port –apparently– as different as the literary work of Roberto Bolaño.